Tingkat Keberhasilan Transaksi, Kemampuan Sistem Teknologi, Kepercayaan, Mutu Layanan E-Banking dan Minat Bertransaksi Ulang Secara Online - I Gusti Agung Anantha; A.A.N. Oka Suryadinatha Gorda (Universitas Pendidikan Nasional, 2017)
The objectives of this study are to know the impacts of Success Transaction Ratio, Technology System Capability, Trust and Service Quality of e-banking in raising customers interest on online transaction in the Bank of BPD Bali. The population of this study are customers who used mobile banking transaction of BPD Bali and the sample took 132 respondents.No probability technique is used in choosing sample. Data analysis applies Structured Equation Model (SEM). The result of the study shows that there are positive impacts which significantly can be seen in the ratio of Success Transaction, Technology system capability, Trust and Service Quality of e-banking in the interest to do online transaction repeatedly at BPD Bali. Therefore, it can be known that the ratio of Success Transaction and the capability of Technology System theoretically and based on this study, are able to convince customers, in addition it is able to increase e-banking service quality which consequently raise the interest to do online transaction repeatedly.However, there are some infrastructures that has to be improved by the corporate.